A REVIEW OF PROVERBS ABOUT BOOKS AND READING IN UZBEK, RUSSIAN, AND ENGLISH (Multidisciplinary Journal of Science and Technology, 2026)
This article examines the role of books in shaping the moral values and worldview of the younger generation in the context of rapid technological and social changes. It highlights the challenges young people face when making ethical choices in modern society. The importance of reading as a key factor in intellectual and spiritual development is emphasized. Using examples from Uzbek, Russian, and English proverbs, the article illustrates the value of books and demonstrates the existence of universal human values across different cultures.